2011
DOI: 10.1007/s00535-011-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-selective β-blockers improve the correlation of liver stiffness and portal pressure in advanced cirrhosis

Abstract: Targeting the hyperdynamic circulation and the increased splanchnic blood inflow by treatment with NSBB unmasks the linear (mechanical) correlation of HVPG and LS in patients with HVPG > 12 mmHg. Measurement of LS by TE is not a feasible method to assess the dynamic components of PHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…LSM has also a good correlation with the stage of cirrhosis, increasing along with HVPG as the Child stage increases [22] . A meta analysis made on 18 studies which included 3644 patients found an overall specificity of 90% (95%CI: 0.81-0.95) and a sensitivity of 79% (95%CI: 0.58-0.91) for LSM by TE in the detection of significant PH [23] .…”
Section: Prediction Of Phmentioning
confidence: 77%
“…LSM has also a good correlation with the stage of cirrhosis, increasing along with HVPG as the Child stage increases [22] . A meta analysis made on 18 studies which included 3644 patients found an overall specificity of 90% (95%CI: 0.81-0.95) and a sensitivity of 79% (95%CI: 0.58-0.91) for LSM by TE in the detection of significant PH [23] .…”
Section: Prediction Of Phmentioning
confidence: 77%
“…The most important are related to technical failure in patients with obesity, and to falsely high results due to conditions unrelated to liver fibrosis (hepatic inflammation, extrahepatic cholestasis, cardiac congestion and meal ingestion [30,31]). While increases in LS over time increase the risk of clinical events in patients with cirrhosis [34], this technique cannot be used to monitor changes in HVPG occurring during treatment with β-blockers for portal hypertension [35]. …”
Section: Introductionmentioning
confidence: 99%
“…They explained this by the fact that mechanisms of PHT become less dependent on the intra-hepatic vascular resistance caused by accumulation of fibrous tissue (as reflected by an increase in LS) above a degree of HPVG, while complex hemodynamic changes (e.g. hyper-dynamic circulation and splanchnic vasodilatation) contribute to the increase in portal pressure that are not assessed by the means of LS (20,23). Accordingly, at higher HPVG levels (where larger OV and hemorrhage risk increases), LS may not be an ideal non-invasive surrogate of HVPG, and, thus, its direct consequence OVs.…”
mentioning
confidence: 99%
“…Even though good correlations have been reported between LS and CSPH, LS measurements may not be good enough at predicting high-risk OVs. Two studies (20,23) stated important findings on the relationship between LS and CSPH, to explain this contradiction. Strong correlation coefficient existed between LS by TE and HVPG values < 12 mmHg, while correlation coefficient dropped to a suboptimal level for HPVG values of ≥ 12 mmHg, which is the threshold for variceal formation and hemorrhage (20,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation